How does the water resources tax affect the sustainable green innovation of water-intensive industrial enterprises? - Xing, Xia; Tang, Honglan; Li, Jie (Frontiers in Environmental Science, 2025)
The global water crisis is intensifying, and scarce water resources have become a critical strategic factor in achieving sustainable development—an issue particularly pressing for China. Existing research on water resource policies predominantly examines the effects of common green innovation among water-intensive enterprises, whereas studies focusing specifically on sustained green innovation remain limited. However, easing water resource pressures and promoting green, high-quality development depend on enterprises’ long-term commitment to green innovation. Therefore, this study employs a Difference-in-Differences (DID) approach to empirically investigate the impact of China’s water resources tax reform on sustained green innovation among water-intensive firms listed on the A-share market from 2012 to 2022, as well as the underlying mechanisms. The empirical results reveal three key findings. First, the water resource tax significantly increases the level of sustained green innovation within these enterprises. Second, the tax promotes continuous innovation by alleviating financing constraints and attracting green investment, and managerial environmental awareness further strengthen this positive effect. Third, state-owned enterprises, large firms, enterprises located in eastern regions, and high-tech firms exhibit more pronounced improvements in sustained green innovation. By uncovering the behavioral responses of enterprises under water resources tax constraints, this study contributes new perspectives to theoretical research on water conservation, emissions reduction, and sustained green innovation. It also provides important policy implications for optimizing green tax instruments to promote sustainable green development and enhance innovation persistence.